The effectiveness of art therapy on motor function in Parkinson’s disease: a systematic review and meta-analysis - Liu, Zexi; Hui, Chen; Liu, Shuhan; Chen, Yujia; Zhang, Yihan; Ye, Wenliang (Frontiers in Psychology, 2025)
ObjectiveThis meta-analysis aimed to evaluate the effectiveness of art therapy interventions in improving motor function performance in patients with Parkinson’s Disease (PD), with a focus on identifying the most effective modalities.MethodRandomized controlled trials were identified through searches in PubMed, Embase, Web of Science, and Cochrane Library. Twenty-six studies were included, assessed for quality, and analyzed following PRISMA guidelines (PROSPERO: CRD42024611770). Subgroup analyses were performed for primary outcomes (UPDRS, TUG, Mini−BESTest), while secondary outcomes (Stride Length, FOG, 6MWT, and Gait Speed) were evaluated using forest and funnel plots to estimate pooled effects.ResultsArt therapy significantly improved motor function, as evidenced by reductions in UPDRS III scores (SMD = −0.44, 95% CI [−0.61, −0.26], p < 0.05), TUG scores (SMD = −0.25, 95% CI [−0.41, −0.10], p < 0.05), and increases in Mini-BESTest scores (SMD = 0.41, 95% CI [0.10, 0.72], p < 0.05). Among the interventions, dance therapy demonstrated the most significant effects on motor function (UPDRS III: SMD = −0.52, 95% CI [−0.78, −0.26], p < 0.05; TUG: SMD = −0.37, 95% CI [−0.58, −0.17], p < 0.05; Mini-BESTest: SMD = 0.56, 95% CI [0.25, 0.87], p < 0.05). Secondary outcomes revealed small to moderate improvements in gait speed (SMD = 0.34, p < 0.05), 6MWT (SMD = 0.41, p < 0.05), FOG (SMD = −0.33, p < 0.05), and stride length (SMD = 0.59, p < 0.05). Although the findings were robust, high heterogeneity in certain outcomes highlights the need for standardized intervention protocols to ensure consistency and reproducibility.ConclusionThis study underscores the clinical significance of art therapy in improving motor functions in PD patients. Among the interventions, dance therapy exhibited the most pronounced effects, highlighting its potential as a pivotal component in multidisciplinary neurorehabilitation programs.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024611770, identifier (CRD42024611770).